Barbecue Fumes: An Overlooked Source of Health Hazards in Outdoor Settings? - Wu, Chen-Chou; Bao, Lian-Jun; Guo, Ying; Li, Shao-Meng; Zeng, Eddy Y. (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2015)
Barbecuing or charcoal-grilling has become part of popular outdoor recreational activities nowadays; however, potential human health hazards through outdoor exposure to barbecue fumes have yet to be adequately quantified. To fill this knowledge gap, atmospheric size-fractioned particle and gaseous samples were collected near an outdoor barbecuing vendor stall (along with charcoal-grilled food items) in Xinjiang of Northwest China with a 10-stage micro-orifice uniform deposit impactor and a polyurethane foam (PUP) sampler and were analyzed for particulate matter and polycyclic aromatic hydrocarbons (PAHs). Exposure to PAHs through inhalation and dermal contact by adult consumers who spent 1 h per day near a charcoal-grilling vendor for a normal meal (lunch or dinner) amounted to a BaP equivalent (BaPeq) dosage of 3.0-77 ng day(-1) (inhalation: 2.8-27 ng day(-1) of BaPeq; dermal contact: 0.2-50 ng day(-1) of BaPeq), comparable to those (22-220 ng day(-1) of BaPeq) from consumer exposure through the consumption of charcoal-grilled meat, assumed to be at the upper limit of 50-150 g. In addition, the potential health risk was in the range of 3.1 X 10(-10) to 1.4 X 10(-4) for people of different age groups with inhalation and dermal contact exposure to PAHs once a day, with a 95% confidence interval (7.2 X 10(-9) to 1.2 X 10(-6)) comparable to the lower limit of the potential cancer risk range (1 X 10(-6) to 1 X 10(-4)). Sensitivity analyses indicated that the area of dermal contact with gaseous contaminants is a critical parameter for risk assessment. These results indicated that outdoor exposure to barbecue fumes (particularly dermal contact) may have become a significant but largely neglected source of health hazards to the general population and should be well-recognized.